Humanoid robot NAO interacting with autistic children of moderately impaired intelligence to augment communication skills - Shamsuddin, Syamimi; Yussof, Hanafiah; Ismail, Luthffi Idzhar; Mohamed, Salina; Hanapiah, Fazah Akhtar; Zahari, Nur Ismarrubie (Elsevier, 2012)
This report presents the findings from our pilot study on the initial behavior of autistic children of moderately impaired intelligence when exposed to simple human-robot interaction (HRI) modules executed by a humanoid robot NAO. All 5 children have been specifically assessed using the Autism Diagnostic Observation Schedule (ADOS) and their diagnosis is classified as autistic disorder. We hypothesize that NAO’s human-like appearance, its capability to blink its eyes, speak and play music; coupled with the simplicity of the HRI modules will be able to entice the children’s interest to engage in communication. Hence, this would significantly reduce the children’s autistic characteristics in communication behavior compared to the usual class setting. In this study, the principal result shows that 4 out of the 5 children exhibited a decrease of autistic behavior (in communication subscale) when the robot is executing HRI modules during the single session of child-robot interaction. This promising outcome indicates that the NAO robot were able to attract the children’s attention, keep each child engaged with the robot during interaction and hence give positive impact to the children’s communication behavior. Relating this to the children’s FSIQ, it can be deducted that autistic children with FSIQ of moderately impaired (from 40-54) are receptive to robotbased intervention. This is again showed by the lower autistic traits observed during the HRI modules compared to in-class setting. Overall, this research suggests that autistic children of moderately impaired intelligence show good response to robot-based intervention. This finding is crucial to form a solid foundation and proof on the positive utilization of the humanoid robot NAO for the children affected by autism.